Dampak Gaya Belajar Siswa pada Konsep Pemahaman Fisika - Hidayat , Nadhifa Muftisany; Ramadany, Nila Ayu; Setiaji, Bayu (Physical Sciences, Life Science and Engineering, 2023)
The COVID-19 pandemic has impacted, changed and forever changed educational institutions from early childhood learning to the adoption of online education at all levels of education. The need for rapidly deployable or deployable strategies requires educators across disciplines to navigate complex logistics and unique situations by immediately employing a variety of instructional technologies through alternative modalities and pedagogical approaches. Some efforts are tried and true, others are unproven and new. Students and instructors are faced with constraints and limitations related to physical work space, as well as challenges and concerns for mental and physical health; all while trying to meet and exceed a number of expectations. Learning styles can be implemented in various learning activities, for example the visual learning style with pictures, and the auditory learning style by listening to the teacher's explanation and friends' opinions (discussing). Understanding student learning styles can make it easier for teachers and educators to choose learning activities and make it easier for students to receive various information.